Північна оборонна лінія римської цитаделі в Ольвії - Хмелевський, Д.М. (Археологія, 2018)
Розглядаються підсумки робіт на ділянці цитадель Ольвійського городища перших століть нової ери, проводиться аналіз розкритих під час цих робіт архітектурнобудівельних залишків північної оборонної лінії римської
цитаделі, комплексу воріт. В статье рассматриваются итоги работ на участке «Цитадель» Ольвийского городища первых веков новой эры.
Проводится анализ архитектурных объектов, керамических комплексов, раскрытых в ходе работ. Даются описание и размеры строительных остатков оборонительных стен, типы кладок. Проведено сравнение открытых ранее
Б.В. Фармаковским на основном раскопе двух куртин (1905—1906 гг.) и выявленной в последнее время части
северо-западной куртины на западном раскопе (2011—2015 гг.).
Открытие «столба» подтверждает верность определения местоположения проема ворот, намеченного
Б.В. Фармаковским на основании выявленных уличных вымосток; размещение такого «столба», скорее всего,
именно рядом с воротами, а не у обычной куртины. The paper deals with the results of work at the “Citadel” site in Olbia of the first centuries CE. The author analyses the
architectural objects and ceramic complexes discovered during the research. The description and dimensions of the building
remnants of the defensive walls, types of masonries are conducted. Comparison of two earlier revealed curtains opened by
B.V. Farmakovskyi at the main excavation (1905—1906) and recently discovered part of the north-western curtain at the
western excavation (2011—2015) is made.
The discovery of the “post” confirms the correctness of the location definition of the gate opening, noted by
B.V. Farmakovskyi on the basis of the identified street impacts; the placement of such “post” is likely to be near the gate,
and not the usual curtain.